Seasonal Variation in the Physiological and Behavioral Responses to Tourist Visitation in Magellanic Penguins - Villanueva, Maria Cecilia (2014)
Penguin colonies are highly visited worldwide. Although several studies have addressed how penguins behaviorally respond to tourist visitation at a point in time, nothing is known about their response across the entire breeding season. Furthermore, behavioral responses are driven by complex physiological processes and the basal physiological state of the individual might affect the way it responds to stimuli. To test the hypothesis that annual changes in corticosterone result from animals having different requirements for expressing (or not) the glucocorticoid-mediated behaviors at different times of the year in the context of tourist visitation, we examined circulating and stress-induced corticosterone in Magellanic penguins (Spheniscus magellanicus) from non-visited areas from the San Lorenzo colony, Peninsula Valdes, Argentina across the breeding season. We also examined the behavioral responses of penguins to a pedestrian approach in tourist-visited and non-visited areas of the colony across the season. Our results showed that circulating levels of corticosterone did not vary across the season; however, stress-induced corticosterone was lowest during molt. Our behavioral results showed that penguins displayed different behavior responses at varying distances depending on the area (visited or non-visited) and stage in the season. Penguins in the tourist area were more tolerant to a human approach than penguins in the non-tourist area. During settlement and molt, penguins showed higher occurrence of behaviors related to self-survival (such as standing, moving farther into the nest, and fleeing), whereas during incubation and chick rearing, penguins displayedmostly a behavior associated with defense and vigilance (such as alternate head turns). Furthermore, penguins allowed a closer approach during incubation, but elicited a subsequent behavior quicker than in the rest of the stages, suggesting that they would be particularly sensitive in this stage. Overall, our results suggest that corticosterone release across the season is more associated with penguins? survival in an extreme environment than with behavioral regulation. From a conservation perspective, we identified that penguins were more sensitive to human approach during incubation, but also molt should be considered as a vulnerable stage because corticosterone secretion is suppressed.